Association between vitamin D receptor (VDR) gene polymorphisms and systemic lupus erythematosus in Portuguese patients. (July 2015) - Carvalho, C; Marinho, A; Leal, B; Bettencourt, A; Boleixa, D; Almeida, I; Farinha, F; Costa, P P; Vasconcelos, C; Silva, B M
Systemic lupus erythematosus (SLE) is a chronic autoimmune disease of unknown origin, in which both genetic and environmental factors are involved. One such environmental factor is vitamin D, a vital hormone that plays a specific function in the immune system homeostasis, acting through a nuclear receptor ( VDR ) expressed in all immune cells. Several polymorphisms of the gene that encodes this receptor have been described. Though inconsistently, these polymorphisms have been associated with clinical manifestations and SLE development. The aim of this study was to determine the possible association between VDR gene polymorphisms (BsmI, ApaI, TaqI e FokI) and SLE susceptibility and severity, in a cohort of lupus patients from the north of Portugal. A total of 170 patients (F = 155, M = 15; age = 45 ± 13.4 years) with SLE (diagnosed according the American College of Rheumatology criteria) with at least five years of disease evolution and followed in the Autoimmune Disease Clinical Immunology Unit of Centro Hospitalar do Porto were studied. Patients and 192 ethnicity-matched controls were genotyped for BsmI (rs1544410), ApaI (rs7975232), TaqI (rs731236) and FokI (rs2228570) polymorphisms by TaqMan allelic discrimination assay. Disease severity was assessed by SLICC damage score, number of affected organs, number of severe flares and pharmacological history. SLE patients with the CT genotype of FokI polymorphism have a higher SLICC value ( p = 0.031). The same result was observed for the group of patients with the TT genotype of TaqI polymorphism ( p = 0.046). No differences were observed in VDR genotype between patients and controls. Also, we observed that the other clinical features analysed were not influenced by VDR polymorphisms. Our study confirms a possible role of VDR gene polymorphisms in SLE. A positive association was found between VDR polymorphisms and SLE severity (chronic damage). The presence of CT genotype of FokI and TT genotype of TaqI seems to confer a worse prognosis and may constitute a risk factor for higher long-term cumulative damage in SLE patients.